Pleomorphic adenoma of palate - Manisha Chauhan Solanki; Sumir Gandhi; George Koshy; Inderjot Singh (Wolters Kluwer Medknow Publications, 2014)
A case of 55-year-old female has been presented, who reported to our centre with an unnoticed painless swelling in the posterior part of hard palate, which was interfering in posterior palatal seal formation during denture fabrication. This swelling was diagnosed as pleomorphic adenoma and complete surgical excision was done along with capsule.